O direito da pessoa com deficiência à avaliação biopsicossocial, multiprofissional e interdisciplinar - Almeida, Silvia Leticia de (2022)
The present study aims to analyze the biopsychosocial assessment as a right of persons with disabilities, in line with the provisions of the UN Convention on the Rights of Persons with Disabilities (CRPD) and the Brazilian Statute on Persons with Disabilities. After outlining the characteristics of the social model of disability, we will demonstrate the indispensable nature of assessing the disabled person under a biopsychosocial, multidisciplinary and interdisciplinary framework in order to break with various segregation models and to recognize the disabled person’s right to dignity, autonomy and equality. Five court decisions will be analyzed, in an effort to demonstrate the mismatch between current legislation and the actual practice of assessing persons with disabilities in processes and procedures that involve their rights – which was the main reason for the choice of this study’s subject. At the end of the study, a proposal for using the Brazilian Registry for Inclusion of Persons with Disabilities (Inclusion Registry) to gather and optimize information resulting from biopsychosocial assessments of persons with disabilities will be presented